Gaining Competitive Advantage through Supply Chain Management - Suresh Reddy, J. (Indian Journal of Marketing, 2005)
Traditionally most organizations have viewed themselves as entities that exist independently from others and indeed need to compete with them in order to survive. There is almost a Darwinian ethic of the "survival of the fittest" driving much of corporate strategy. However such a philosophy can be self defeating if it leads to an unwillingness to cooperate in order to compete. Behind this seemingly paradoxical concept is idea of supply chain integration. In the past it was often the case that relationships with suppliers and downstream customers (distributors or retailers) were adversial rather than cooperative.It is still the case today some companies will seek to achieve cost reductions or profit improvement at the expense of their supply chain partners. Companies of above character donot realize that simply transferring costs upstream or downstream does not make them any more competitive. The reason for this is that ultimately all costs will make their way to the final market place to be reflected in the price paid by the end user. The leading edge companies recognize the fallacy of this conventional approach and instead seek to make the supply chain as a whole, more competitive through the value it adds and the costs that it reduces overall. They have realized that the real competition is not company against company but rather supply chain against supply chain.